Ateliê de figurinhas com arte de resistência - Arantes, Daryellen Ramos (2023)
This research was articulated around the following problem: how do people who make images of resistance see, can they see themselves and make images of resistance be seen? We bring conceptual issues arising from the practices of a studio designed, amid the challenging context of the COVID-19 pandemic, from the perspective of Visual Culture studies, to discuss actions used in the creation and development of a creative environment for editing stickers with frames of films screened at “They make cinema: a showcase for films directed by women”. The research collaborators were invited through posters, posted on informative bulletin boards of the Uniforte network cooperatives, announcing remote meetings to exercise ways of appreciating, capturing and editing stickers. Using a/r/tography as a methodological approach, we dialogue with the demand in order to understand fundamentals and mediation strategies aimed at artistic proposals in exercises related to the construction of the gaze. The research resulted in the production of a collection of film links for the sticker studio. The study also established connections with image makers of resistance from the Uniforte cooperatives. The authors used in the bibliography offer a theoretical framework to deal with the themes of resistance, poetics of solidarity, education for visual culture, visualities, decolonial pedagogies, art research and other cross cutting themes.